Studies on Schismatoglottideae (Araceae) of Borneo XXV: a diminutive new Piptospatha from Sabah - Boyce, P.C; Wong, Sin Yeng (Taylor & Francis Ltd., 2013)
A diminutive new species of Piptospatha, P. loi P.C. Boyce and S.Y. Wong, is described from waterfalls over basalt in E Sabah. Overall, it is most similar to P. pileata S.Y. Wong and P.C. Boyce (Kalimantan Timur, obligated to shales), but differs in several features of the inflorescences and leaves. The new species is illustrated from living plants.